Intra-regional trade in East Asia: The decoupling fallacy, crisis, and policy challenges - Prema-chandra Athukorala; Archanun Kohpaiboon (Asian Development Bank Institute (ADBI), 2009)
This paper examines the export experience of East Asian economies in the aftermaths of the crisis against the backdrop of a systematic analysis of precrisis trade patterns. The analysis is motivated by the decoupling thesis, which was a popular theme in Asian policy circles in the lead-up to the onset of the recent financial crisis, and aims to probe three key issues: Was the East Asian trade integration story that underpinned the decoupling thesis simply a statistical artifact or the massive export contraction caused by an overreaction of traders to the global economic crisis and/or by the drying up of trade credit, which overpowered the cushion provided by intra-regional trade? What are the new policy challenges faced by the East Asian economies? Is there room for an integrated policy response that marks a clear departure from the precrisis policy stance favoring export-oriented growth? The findings serve to caution against a possible costly backlash against openness to foreign trade arising from the newfound enthusiasm for rebalancing growth (redressing the strong bias for exports in development policy), and make a strong case for a well-coordinated strategy to fight new protectionism, as part of a long-term commitment to nondiscriminatory multilateral and unilateral trade liberalization.
Keywords: F14; F15; O9; 330; Finanzmarktkrise; Außenhandelseffekt; Internationale Arbeitsmobilität; Außenhandelsstruktur; Ostasien